2016
DOI: 10.1126/scitranslmed.aad9922
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus α toxin potentiates opportunistic bacterial lung infections

Abstract: S. aureus α toxin promotes opportunistic co-infection, which can be neutralized with a pathogen-specific antibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 62 publications
9
108
0
1
Order By: Relevance
“…We therefore tested the ability of KPE33 to reduce bacterial bur- den in the lungs of mice systemically depleted of neutrophils. As previously reported, bacterial burden in the lungs of mice 24 hours after infection was the same in control mice and in mice treated with an anti-Ly6G antibody (1A8) to deplete neutrophils (500 μg/mouse) ( Figure 2D and Supplemental Figure 5A) (18). Prophylaxis with KPE33 significantly (P < 0.0001) reduced bacterial CFU recovered from the lungs 24 hours after infection in control mice but not in neutrophil-depleted mice, suggesting that the protective activity of KPE33 was mediated to a substantial degree by neutrophil engagement.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…We therefore tested the ability of KPE33 to reduce bacterial bur- den in the lungs of mice systemically depleted of neutrophils. As previously reported, bacterial burden in the lungs of mice 24 hours after infection was the same in control mice and in mice treated with an anti-Ly6G antibody (1A8) to deplete neutrophils (500 μg/mouse) ( Figure 2D and Supplemental Figure 5A) (18). Prophylaxis with KPE33 significantly (P < 0.0001) reduced bacterial CFU recovered from the lungs 24 hours after infection in control mice but not in neutrophil-depleted mice, suggesting that the protective activity of KPE33 was mediated to a substantial degree by neutrophil engagement.…”
Section: Resultssupporting
confidence: 60%
“…Currently, mAbs have been approved or are in development for numerous infectious diseases, including RSV, influenza, Pseudomonas aeruginosa, and Staphylococcus aureus (18,20,(29)(30)(31)(32). These mAbs target secreted virulence factors, surface/structural proteins, or both, resulting in neutralization of pathogen-induced host damage and improved pathogen clearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach currently in clinical development is the prevention or treatment of S. aureus pneumonia with a MAb targeting AT, MEDI4893*, and AR-301 (11). AT is a cytolytic pore-forming toxin reported to have a number of effects in S. aureus pneumonia models such as cell death, inducing ADAM10-mediated cleavage of epithelial tight cell junctions, stimulating a damaging proinflammatory cytokine response, and altering bacterial processing within alveolar macrophages (19)(20)(21)(22). Although a definitive role for AT in human pneumonia has yet to be defined, Stulik et al recently reported that AT expression levels by colonizing 10 (CFU/lung) (C), log 10 (CFU/spleen) (D), and log 10 (CFU/kidneys) (E) for rabbits (n ϭ 12 animals per experimental group) that were randomized to receive (i) 30 mpk c-IgG at 1.5 hpi; (ii) 30 mpk MEDI4893* at 1.5 hpi; (iii) 50 mg/kg linezolid at 1.5, 10, 18, and 26 hpi; and (iv) 30 mpk MEDI4893* at 1.5 hpi and 50 mg/kg linezolid at 1.5, 10, 18, and 26 hpi with USA300/SF8300 wild-type strain.…”
Section: Discussionmentioning
confidence: 99%
“…Естественные антитела защищают макроорганизм от антигенов (например, капсульных полисахаридов), которые не вызывают монореактивный антительный от-вет [17]. Так как естественные антитела постоянно присутствуют в сыворотке крови, антигены пато-генных агентов, в частности бактерий Staphylococcus aureus, сразу после инфицирования взаимодей-ствуют с данными антителами [16,24]. Необходимо отметить, что CD5 + CD11b -В 1a -клетки представля-ют собой долгоживущие лимфоциты и их потеря может быть необратимой.…”
Section: â 1 -êëåòêèunclassified